Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Pegawai Universitas Buana Perjuangan Karawang - Sihabudin Sihabudin (Politeknik Ganesha Medan, 2021)
One of the variables that have a major effect on employee engagement is leadership style. In addition, one of the factors that influence employee efficiency is leadership. Since it is important to pay attention to two points at the top, it is important to pay attention to leadership style. Employee success is one of the most powerful variables in the workplace. Employees of Administration Universitas Buana Perjuangan Karawang, a total of 104 people, were studied from January to March 2020, with a total sample size of 82 people. The research employs a quantitative approach that is processed using the application SPSS 20. The data is collected through interviews, evaluation, and a Google Form Sample to deploy a questionnaire. Universitas Buana Perjuangan Karawang